De-escalation of Empiric Antibiotics Following Negative Cultures in Hospitalized Patients With Pneumonia: Rates and Outcomes. (4th March 2020) - Deshpande, Abhishek; Richter, Sandra S; Haessler, Sarah; Lindenauer, Peter K; Yu, Pei-Chun; Zilberberg, Marya D; Imrey, Peter B; Higgins, Thomas; Rothberg, Michael B
Abstract: Background: For patients at risk for multidrug-resistant organisms, IDSA/ATS guidelines recommend empiric therapy against methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas . Following negative cultures, the guidelines recommend antimicrobial de-escalation. We assessed antibiotic de-escalation practices across hospitals and their associations with outcomes in hospitalized patients with pneumonia with negative cultures. Methods: We included adults admitted with pneumonia in 2010–2015 to 164 US hospitals if they had negative blood and/or respiratory cultures and received both anti-MRSA and antipseudomonal agents other than quinolones. De-escalation was defined as stopping both empiric drugs on day 4 while continuing another antibiotic. Patients were propensity adjusted for de-escalation and compared on in-hospital 14-day mortality, late deterioration (ICU transfer), length-of-stay (LOS), and costs. We also compared adjusted outcomes across hospital de-escalation rate quartiles. Results: Of 14 170 patients, 1924 (13%) had both initial empiric drugs stopped by hospital day 4. Hospital de-escalation rates ranged from 2–35% and hospital de-escalation rate quartile was not significantly associated with outcomes. At hospitals in the top quartile of de-escalation, even among patients at lowest risk for mortality, the de-escalation rates were <50%. In propensity-adjusted analysis, patients with de-escalation had lower odds of subsequent transfer to ICU (adjusted odds ratio, .38; 95% CI, .18–.79), LOS (adjusted ratio of means, .76; .75–.78), and costs (.74; .72–.76). Conclusions: A minority of eligible patients with pneumonia had antibiotics de-escalated by hospital day 4 following negative cultures and de-escalation rates varied widely between hospitals. To adhere to recent guidelines will require substantial changes in practice. Abstract : Less than 15% of eligible patients with pneumonia had antibiotics de-escalated immediately following negative cultures and de-escalation rates varied widely among hospitals. To adhere to newly published guidelines, hospitals will have to change practice substantially.